Perlindungan Dan Pengelolaan Hak Royalti Pencipta MelaluiPeraturan Pemerintah No 56 Tahun 2021 - Gracelina Jesyca Carmety Nyaman; Kadek Nita Erlita; Anjalia Rambu Kahi; Ruhil Amani (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2021)
In making this article to get an overview of the protection and management of royalty rights in Government Regulation No. 56of 2021, which guarantees protection and legal certainty for the economic rights of creators, copyright holders, and relatedrights owners to songs and / or music, is needed. there is a royalty management mechanism that is transparent, high quality,and right on target as well as through the means of Information Technology. Therefore music is one of the most importantparts in human life. Based on the existing reality that music is the most important part of life, it is hoped that this informationon classical music can meet the needs of society and the classical music community. In carrying out musical activities, theconcept of Elegance of melody is used which can create a space for a combination of romantic and contemporary times thatcan create a spatial atmosphere that seems classic, romantic, but incorporates a contemporary color. Number 28 of 2014concerning Copyright, especially Article 15 where Royalty Rights for creators, copyright holders, and related rights owners whoare not known and / or have not been a member of an LMK are kept and announced by LMKN for 2 (two) years for the creatorsto know , copyright holders, and voters related rights. Within the LMKM always strives to increase royalty revenue for the useof songwriting and music in Indonesia and distribute Royalties for the use of songwriting and music works to rights ownersthrough LMK in a fair, transparent and accountable in accordance with applicable regulations.